High-efficiency inorganic perovskite solar cell based on a stripping and idling assisted growing technique - YAN Huibo; ZHOU Dingjian; HUANG Jincheng; LIU Jun; WANG Ming; LUO Zhongming; LUO Xi; TIAN Mengyao; ZHENG Ting; LI Guijun; XU Ping (Shenzhen Daxue xuebao. Ligong ban)
Cesium lead iodide dibromide (CsPbI2Br) perovskite is an ideal material for inorganic perovskite solar cells due to its suitable tolerance factor and good thermal stability. However, the defects of low power conversion efficiency and poor device reproducibility hinder the further improvement of the performance of inorganic CsPbI2Br solar cells. By studying the preparation process of CsPbI2Br inorganic perovskite solar cells, we find that the film-forming environment has a great influence on the uniformity, optical properties and device performance repeatability of CsPbI2Br films. In this paper, a stripping and idling assisted growing process strategy is proposed to obtain CsPbI2Br films with large grain size, high crystallinity, and low trap-defects density. The power conversion efficiency of CsPbI2Br perovskite solar cells reaches 14.1%. More importantly, this method greatly reduces the influence of ambient conditions on the film quality and improves the reproducibility of the device.